FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM MELAKSANAKAN KEWAJIBAN PERPAJAKAN - Afina Mustika; Junawan Junawam; Mika Debora BR. Barus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Taxes are one of the largest sources of state revenue and income. MSME tax is one of the incomes that has a significant impact and a large contribution to the level of the economy in Indonesia on a micro basis. The purpose of this study was to analyze the effect of tax socialization, taxpayer awareness, and tax sanctions on MSME taxpayer compliance. The population of this study is the owners of SMEs selected randomly. The research sample amounted to 51 respondents obtained by random sampling technique. The data used is primary data collected using a questionnaire. This study uses multiple linear regression with the help of SPSS. The results of this study indicate that knowledge and understanding of taxation, tax service quality tax policies and tax socialization have a significant effect on MSME taxpayer compliance in Batu City in carrying out tax obligations.Keywords: Taxpayer compliance, taxpayer awareness, tax sanctions, tax socialization.